Vulnerability assessment and blue carbon potential of two mangrove sites in Malaysia / Teh Lay Hoon - Teh, Lay Hoon (2015)
Coastal blue carbon is an emerging subject in climate change science which looks into coastal habitats such as mangrove forests for its ability to sequester and store carbon from the atmosphere. Mirroring the concept of “Reducing Emissions from Deforestation and Forest Degradation” (REDD+), the concept of coastal blue carbon is also about the incentives given in return for preserving these coastal habitats for its role in climate change mitigation. As mangrove forests in Malaysia are facing rapid rate of degradation, this study is about assessing the coastal blue carbon as a viability to facilitate better mangrove conservation measures in Malaysia through its incentives. For this study, two mangrove forest sites were selected from southern Johor to determine the level of vulnerability that these habitats are facing, while taking into consideration of the current management and policy in place. For this assessment, the baseline information of the study sites were collected and used in developing criteria to which the vulnerability assessment was conducted. The aim of the vulnerability assessment is to identify the prevailing threats on mangrove forests and establish the notion that the current conservation approaches may not be sufficient to protect these habitats. As a following step, the Rapid Impact Assessment Matrix (RIAM) were used as a tool to evaluate the benefits of implementing coastal blue carbon in the current management approach. Subsequently, gaps and challenges faced by the current management and policies relating to mangrove conservation in Malaysia were identified, and case studies were conducted as a mean to ascertain how best the coastal blue carbon mechanism can be adapted into the current structure for it to be effective. The research shows that while the mangrove in Malaysia has a large carbon storage potential, the prevailing threats currently faced by the vulnerable mangrove forests are quickly diminishing its capacity. It was also found that there is a need for Malaysia to establish an extensive network of collaborations among the relevant agencies within the country, with concerting efforts from non-governmental organisations and academic institutions in working towards proper carbon measurement and accounting. The main aim is for a change in policy which can ensure that the protection of mangrove areas are accounted more distinctively in the current policies and legislations. Given that the importance of mangrove can be made quantifiable as an incentive in terms of carbon credits and climate change mitigation, the conservation priority for mangrove could be significantly increased.